FAKTOR YANG MEMPENGARUHI STATUS IMUNISASI HB.0 PADA BAYI UMUR 0-7 HARI DI WILAYAH KERJA PUSKESMAS SUKABUMI - Rasmiatin Rasmiatin; Mega Silvian N.; Tutik Ekasari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Hepatitis B is an infectious disease caused by the Hepatitis B Virus (HBV). The aim of the study was to analyze the factors that influence the status of HB.0 immunization in infants aged 0-7 days in the working area of the Sukabumi Public Health Center, Probolinggo City. The research design in this research is correlational analytic research. The population in this study were mothers who had babies aged 0-7 days in the work area of the Sukabumi Health Center in April-June 2022 as many as 30 people. The number of samples is 30 people with Total Sampling sampling technique. Collecting data using a questionnaire then the data is processed using SPSS using Chi square and logistic regression. The results of the analysis show that knowledge is sufficient knowledge, namely 19 people (63.3%), Middle school education 12 people (40%), positive attitude 20 people (70%), birth attendants by midwives 20 people (66.7%), delivery places at BPS 11 people (36.7%), 20 people (66,7%) made a neonatal visit, 19 people were inactive (63.3%) while the results of the Chi square test showed a relationship between education (0.038), attitude (0.001), place of delivery ( 0.007), neonatal visit (0.011), activeness of officers (0.06) with immunization status obtained p-value less than 0.05. The lack of coverage of Hb-0 immunization in infants born 0-7 days is caused by several factors, including deliveries that are not assisted by professional health workers and even those who are not assisted by health workers such as mothers giving birth themselves, assisted by traditional birth attendants and so on. born not given Hb-0 . immunization